2021
DOI: 10.5603/ep.a2021.0036
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio with bone mineral density in adolescent girls suffering from anorexia nervosa

Abstract: Introduction: Inflammation is supposed to be one of the factors contributing to decreased bone mineral density (BMD) in anorexia nervosa (AN). The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are simple and cost-effective inflammatory markers, well documented as indicators of postmenopausal osteoporosis. This study aimed to assess the relationships between these ratios and BMD in girls with AN. Material and methods:The electronic records of 73 girls hospitalized for AN were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…Baseline low s-and TB-BMD Zscores were observed in 12/75 (16.0%) and 28/75 (37.3%) of the patients, respectively. Similar results were observed in our earlier research [34]. Moreover, nutritional indices, OC, and the OPG/sRANKL ratio were lower while the duration of the disease was longer in low sand TB-BMD.…”
Section: Table 3 Correlation Between Plasma Chemerin Clinical and Ant...supporting
confidence: 91%
See 2 more Smart Citations
“…Baseline low s-and TB-BMD Zscores were observed in 12/75 (16.0%) and 28/75 (37.3%) of the patients, respectively. Similar results were observed in our earlier research [34]. Moreover, nutritional indices, OC, and the OPG/sRANKL ratio were lower while the duration of the disease was longer in low sand TB-BMD.…”
Section: Table 3 Correlation Between Plasma Chemerin Clinical and Ant...supporting
confidence: 91%
“…Consequently, it may contribute to loss of bone mass. It should also be emphasized that the presented results confirm our earlier observation [34] that BMD differs depending on the examined skeletal area in adolescent girls with AN. Cortical bone is more severely affected than trabecular bone.…”
Section: Table 3 Correlation Between Plasma Chemerin Clinical and Ant...supporting
confidence: 91%
See 1 more Smart Citation
“…Among the various hematological and immunological abnormalities documented in AN [19][20][21][22], bone marrow degeneration has been linked to the severity of weight loss [23], while concentrations of the chemokine CCL11 seem to be inversely related to Body Mass Index (BMI) [24]. Furthermore, the neutrophil-to-lymphocyte ratio (NLR) and platelet-tolymphocyte ratio (PLR) showed significant correlations with lower BMI [17] and alterations in bone mineral density [25]. Changes in bone mineral density have also been associated with leptin and adiponectin levels [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still unclear whether the witnessed disturbances in peripheral white blood cells is related to a primary immunological predisposition in patients with AN or to a non speci c end result due to malnutrition [28]. To date, the only study evaluating NLR in patients with AN has demonstrated that it is inversely correlated to bone mineral density due to in ammation's effect on bone mineralization in adolescent girls [29]. To our knowledge, there is no study that assesses the impact of CM on the immune system of patients with AN as re ected by the NLR.…”
Section: Introductionmentioning
confidence: 99%